2011
DOI: 10.1128/cvi.00076-11
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 Cytokine Profile in Patients Coinfected with HIV and Leishmania in Brazil

Abstract: To evaluate the effects of HIV on immune responses in cutaneous leishmaniasis (CL), we quantified cytokine levels from plasma and stimulated peripheral blood mononuclear cells (PBMCs) from individuals infected with HIV and/or CL. Gamma interferon (IFN-␥) and interleukin 13 (IL-13) levels and the ratio of IFN-␥ to IL-10 produced in response to stimulation with soluble Leishmania antigens were significantly lower in HIV-Leishmania-coinfected patients than in CL-monoinfected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In HIV-VL co-infection, the Th2 response that is characteristic of VL is exaggerated, with decreased levels of IL-12 and IL-18 and IFN-γ [30] . In HIV and CL co-infected patients, a similar change was not found in a study with a limited number of patients who had normal IFN-γ levels, but this change may underlie more severe cutaneous disease [31] . Patients co-infected with HIV and tegumentary leishmaniasis (the term used in South America to denote CL, MCL, or DCL) were shown to have decreased absolute numbers of effector and central memory CD4 cells with decreased function as demonstrated by response to stimulation with Leishmania antigen [32] ; however, this defect is not as profound as in HIV-VL co-infections (>350 and <200 CD4 cells/mm 3 , for tegumentary and visceral leishmaniasis, respectively) [33] .…”
Section: Immune Responses In Hiv and Leishmaniasis Co-infectionsupporting
confidence: 57%
“…In HIV-VL co-infection, the Th2 response that is characteristic of VL is exaggerated, with decreased levels of IL-12 and IL-18 and IFN-γ [30] . In HIV and CL co-infected patients, a similar change was not found in a study with a limited number of patients who had normal IFN-γ levels, but this change may underlie more severe cutaneous disease [31] . Patients co-infected with HIV and tegumentary leishmaniasis (the term used in South America to denote CL, MCL, or DCL) were shown to have decreased absolute numbers of effector and central memory CD4 cells with decreased function as demonstrated by response to stimulation with Leishmania antigen [32] ; however, this defect is not as profound as in HIV-VL co-infections (>350 and <200 CD4 cells/mm 3 , for tegumentary and visceral leishmaniasis, respectively) [33] .…”
Section: Immune Responses In Hiv and Leishmaniasis Co-infectionsupporting
confidence: 57%
“…HIV/ Leishmania co-infected patients also present a reduction in the lymphoproliferative response to Leishmania antigens associated with the decreased quantity of both effector memory and central memory CD4 + T-cells ( Góis et al, 2014 ). A reduction in the IFN-γ and IL-13 levels and the ratio of IFN-γ/IL-10 produced in response to stimulation with soluble Leishmania antigens were also observed in individuals infected with HIV and/or cutaneous leishmaniasis ( Rodrigues et al, 2011 ). They suggested that alterations in cytokines expression create a microenvironment that favors the replication and the spread of the Leishmania parasites, leading to the dissemination of cutaneous infection and the visceralization of typically dermotropic species ( Rodrigues et al, 2011 ).…”
Section: The Host Point Of Viewmentioning
confidence: 98%
“…Additionally, elevated pro-inflammatory cytokine production is considered to be a predictor of IRIS development in HIV-infected patients at the onset of HAART [ 26 ]. Considering the plasma levels of TNF-α in two HIV-uninfected patients with active mucocutaneous leishmaniasis evaluated at our laboratory (22 pg/mL and 13 pg/mL) [ 27 ], the levels observed in this patient during IRIS were similar. Following treatment with Amphotericin B and corticosteroids, an increase in plasmatic IFN-γ, as well as in the IFN-γ/IL-10 ratio, was observed in the present case, while TNF-α remained stable.…”
Section: Discussionmentioning
confidence: 96%